2020
DOI: 10.1007/s00330-020-07273-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and interobserver variability of CO-RADS in patients with suspected coronavirus disease-2019: a multireader validation study

Abstract: Objective To conduct a multireader validation study to evaluate the interobserver variability and the diagnostic accuracy for the lung involvement by COVID-19 of COVID-19 Reporting and Data System (CO-RADS) score. Methods This retrospective study included consecutive symptomatic patients who underwent chest CT and reverse transcriptase-polymerase chain reaction (RT-PCR) from March 2020 to May 2020 for suspected COVID-19. Twelve readers with different levels of expertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 18 publications
8
63
1
4
Order By: Relevance
“…However, if there were real lobar pneumonias or "tree in bud" patterns, the agreement would have been higher. Our results are in line with those of several previous studies [ 15 , 23 , 28 , 31 , 32 ]. Prokop et al [ 15 ] conducted the first study that investigated the consistency of CO-RADS and reported a reasonable level of moderate intra-reviewer agreement ( κ = 0.47), with the highest agreement noted for CO-RADS 1 ( κ = 0.58) and 5 ( κ = 0.68).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, if there were real lobar pneumonias or "tree in bud" patterns, the agreement would have been higher. Our results are in line with those of several previous studies [ 15 , 23 , 28 , 31 , 32 ]. Prokop et al [ 15 ] conducted the first study that investigated the consistency of CO-RADS and reported a reasonable level of moderate intra-reviewer agreement ( κ = 0.47), with the highest agreement noted for CO-RADS 1 ( κ = 0.58) and 5 ( κ = 0.68).…”
Section: Discussionsupporting
confidence: 94%
“…Meanwhile, the sensitivity significantly increased for both systems when excluding the asymptomatic/mild patients and considering only moderate (sensitivity = 94.7%) and severe/critically ill patients (sensitivity = 97.8%); this is not surprising, taking into account that the sensitivity depends on CT imaging features, which have been considerably proven in several recent studies [ 6 , 18 22 ], while CT has been confirmed to be a reliable imaging approach for the evaluation of COVID-19. Our data are congruent with the results mentioned in previous research [ 15 , 23 28 ], which suggested that the CO-RADS and the RSNA chest CT classification system performed very well in predicting COVID-19 in patients with moderate to severe symptoms. Notably, a recent meta-analysis published by Kwee et al [ 29 ] concluded that COVID-19 infection frequency was higher in patients categorized with higher CO-RADS and RSNA classification categories.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For reference, we have also included the performance of the manually rated CO-RADS scoring system by a radiologist on the same test set, which had sensitivity/specificity of 74%/71%. The reported performance of CO-RADS in identifying COVID-19 (positive RT-PCR) is variable in literature with Bellini et al reporting sensitivity/specificity of 71.0%/81.0% [18], Lieveld et al reporting sensitivity/specificity of 89.4%/87.2% [19], and Prokop et al reporting sensitivity/specificity of 90%/82.8% [16].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of chest CT scans of 572 symptomatic patients (142 with RT-PCR confirmed COVID-I n p r e s s with a substantial agreement for CO-RADS 1 category (Fleiss' k = 0.61) and moderate agreement for CO-RADS 5 category (Fleiss' k = 0.60). CO-RADS score ≥ 4 was identified by ROC analysis as the optimal threshold with a cumulative area under the curve of 0.72, sensitivity 61%, and specificity 81% (42).…”
Section: What Reporting Systems Have Been Found Useful For Conveying mentioning
confidence: 99%